Hydrothermal Carbonization of Eucheuma cottonii for Selective Adsorption of Anionic Dyes - Putri, Bunga Indah; Arsyad, Fitri Suryani; Lesbani, Aldes (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2024)
The contamination of wastewater with synthetic dyes, particularly anionic dyes, poses a significant environmental challenge due to their persistence and difficulty in removal. Traditional adsorbents are often expensive or inefficient, driving the need for sustainable, eco-friendly alternatives. In response to this problem, this study explores the use of Eucheuma cottonii, a fast-growing and widely available macroalgae, as a raw material for producing hydrochar through hydrothermal carbonization (HTC). The goal is to develop a renewable and effective adsorbent capable of selectively removing anionic dyes from contaminated water. Hydrochar was synthesized at two different HTC temperatures, 150°C and 250°C, and its surface properties were characterized using FT-IR and BET analyses. Adsorption experiments were conducted on four anionic dyes-Congo Red (CR), Direct Yellow (DY), Methyl Orange (MO), and Direct Green (DG)-under varying pH, contact time, dye concentration, and temperature conditions. The hydrochar produced at 250°C (HC-250) demonstrated the highest surface area and pore volume, leading to superior adsorption performance, particularly for DY. Kinetic studies revealed a chemisorption-driven mechanism, while thermodynamic analysis confirmed the adsorption process to be spontaneous and endothermic, with both chemisorption and physisorption contributing to dye removal. The adsorption behavior followed the Langmuir isotherm model, indicating monolayer adsorption, with minimal interaction between adsorbed molecules. Regeneration tests confirmed that Eucheuma cottonii hydrochar could be reused over multiple cycles with minimal efficiency loss. Future work could optimize the HTC process by adjusting pressure, heating rates, and pre-treatment methods to improve adsorption properties. Incorporating nanomaterials or metal oxides could enhance adsorption for a wider range of pollutants, while machine learning could predict adsorption behavior under different conditions. Additionally, exploring the hydrochar’s use in energy storage or as a catalyst offers promising applications. Life-cycle assessments (LCAs) and techno-economic analyses (TEAs) will be vital for assessing scalability and environmental impact, positioning Eucheuma cottonii hydrochar as a sustainable, multifunctional material for industrial applications.